ONE ROOF JUDICIAL SYSTEM IN INDONESIA - Sufiarina, Sufiarina; Fakhriah, Efa Laela (UI Scholars Hub, 2012)
Judicial power as an independent and autonomous power must be free from any intervention and power, thus ensuring that judges possess independence and impartiality in handling cases. One of the measures for enhancing the independence and autonomy of the judiciary is by placing it under the one roof judicial arrangement developed by the Supreme Court, both from the judicial as well as the non-judicial technical aspects. Up to the present time, endeavors for bringing the four court jurisdictions under the one roof judicial arrangement developed by the Supreme Court have not been completely materialized, due to the existing dualism in judicial power at various courts. The objective of this research is to understand the developments in the endeavors towards bringing the Indonesian judicial system under the one roof judicial arrangement developed by the Supreme Court. The type of research applied is descriptive normative juridical research, namely legal research based on examining secondary data. As the research results indicate, the one roof system developed by the Supreme Court is already being implemented, with the exception of the Military Court and the Tax Court within the State Administration Court jurisdiction.